GENETIC STUDY OF GRAIN MORPHOLOGICAL TRAITS AND RELATION TO GRAIN YIELD IN BREAD WHEAT GENOTYPES - KSHITIZ KUMAR PAWAR; DEVENDRA K. PAYASI; A. K. SINGH (The Bioscan, 2015)
Present investigation includes six bread wheat cultivars with fifteen F1‘s hybrid in three replications using randomized block design (RBD). ANOVA for combining ability revealed that non-additive components of genetic variation were present in governing the inheritance of all grain characteristics, Therefore, good success can be achieved when selection for number of grains per panicle (GW-273), grain length and grain width (C- 306),having a high value of gca. Characteristics with a high sca can be used for hybrid wheat production or application haploid production via anther culture on F1‘s progenies, (HW-147/GW-273, GW-273/C-306, HD- 2864/HW-147 and HI-1544/HD-2864). Thus, it is also suggested from these results that selection for the right characteristics will ensure to improvement of more than one characteristic simultaneously, due to the correlation among different traits. The results obtained from this study might be helpful for wheat breeders trying to develop new varieties with better grain features to improve the milling and baking quality of wheat.